EVALUASI PROGRAM PENINGKATAN KUALIFIKASI SARJANA (S-1) BAGI GURU MADRASAH IBTIDAIYAH DAN GURU PENDIDIKAN AGAMA ISLAM PADA SEKOLAH MELALUI DUALMODE SYSTEM DI STAIN PONOROGO - Drs. Ju'subaidi.,M.Ag (El-QUDWAH, 2013)
EVALUASI PROGRAM PENINGKATAN KUALIFIKASI SARJANA (S-1) BAGI GURU MADRASAH IBTIDAIYAH DAN GURU PENDIDIKAN AGAMA ISLAM PADA SEKOLAH MELALUI DUALMODE SYSTEM DI STAIN PONOROGO  Oleh:Drs. Ju’subaidi, M, Ag. Dosen STAIN Ponorogo Email: subaidi_6@yahoo.com   ABSTRACT The research aim is to know the efective program of the dual mode system in developping of the teachers’ qualification in the elementery school of madrasah and the Islamic educational teachers’ qualification of elementery school. It uses the qualitative approach by evaluation design. The data collection with observation, interview by supporting the documentation technique. The data is analyzed by interactive analyzed which comprise data reduction, data display and conclusion or drawing. The results are only the phisych preparation without any understanding concept to cause the chaos in implemented program. The implementation doesn’t concord the framework of the program which raises in-efficiency and the cost increasing. Keyword : Dual Mode System, Interactive Analyze, Framework, in-efficiency